Obtenção de nanopartículas de hexaferrita de bário pelo método pechini - Galvão, Sheila Bernhard (2010)
In this study barium hexaferrite was (general formulae BaFe12O19) was synthesized by the Pechini method under different conditions of heat treatment. Precursors like barium carbonate and iron nitrate were used. These magnetic ceramic, with magnetoplumbite type structure, are widely used as permanent magnet because of its excellent magnetic properties, such as: high Curie temperature, good magnetic anisotropy, high coercivity and corrosion resistance. The samples were characterized by thermal analysis (DTA and TG), X- ray Diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), Scanning Electron Microscopy (SEM) end Vibrating sample Magnetometer (VSM). The results confirm the expected phase, which was reinforced according to our analysis. A single phase powder at relatively high temperatures with particle sizes around 100 nm was obtained. The characteristic magnetic behavior one of the phases has been noted (probably superparamagnetic material), while another phase was identified as a ferrimagnetic material. The ferrimagnetic phase showed vortex configuration with two central and slightly inclined plateaus. In general, increase of heat treatment temperature and time, directly influenced the technological properties of the samples